1990
DOI: 10.2105/ajph.80.5.599
|View full text |Cite
|
Sign up to set email alerts
|

Passive smoking and 20-year cardiovascular disease mortality among nonsmoking wives, Evans County, Georgia.

Abstract: The association ofpassive smoking and cardiovascular disease (CVD) mortality was assessed in a cohort of 513 rural, married Black and White women who were disease-free and selfdescribed as never-smokers at baseline in 1960. Over a 20-year period, 76 of 147 total deaths were attributed to CVD. Relative risk estimates adjusted for age, cholesterol, blood pressure, and body mass from proportional hazards models were 1.59 for CVD (95% CI = 0.99, 2.57) and 1.39 (CI = 0.99, 1.94) for all cause mortality among women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 15 publications
0
44
0
2
Order By: Relevance
“…Tobacco smoking has a pressing effect on the vessels, resulting in the development of arterial hypertension. Results of meta-analyses performed by several independent research centres have revealed a connection between passive smoking and CVD [20][21][22][23][24][25]. Low level of physical activity was the next problem in the population examined in our study; 46% of the participants (42% men and 54% women) did not practise any kind of physical activity during leisure time.…”
Section: Psychological Factorsmentioning
confidence: 68%
“…Tobacco smoking has a pressing effect on the vessels, resulting in the development of arterial hypertension. Results of meta-analyses performed by several independent research centres have revealed a connection between passive smoking and CVD [20][21][22][23][24][25]. Low level of physical activity was the next problem in the population examined in our study; 46% of the participants (42% men and 54% women) did not practise any kind of physical activity during leisure time.…”
Section: Psychological Factorsmentioning
confidence: 68%
“…To ensure completeness, we reviewed published and unpublished studies of nonfatal myocardial infarction (MI) and/or death from ischemic heart disease (IHD) among lifelong nonsmokers whose potential ETS exposure was defined by the smoking status of the spouses. Ultimately we included nine cohort (3,4,(6)(7)(8)(9)(10)(11)(12)(13) and eight case-control (14)(15)(16)(17)(18)(19)(20)(21)(22) studies in the overview. Two of the cohort studies (3,4) and three case-control studies (20)(21)(22) were new since OSHA last summarized the literature (5).…”
Section: Methodsmentioning
confidence: 99%
“…Spousal environmental tobacco smoke and coronary heart disease: case-control studies (listed by first author). Hirayama, 1984 (6) Svendsen, 1987 (9) Butler, 1988 (spouse-pairs) (10) Butler, 1988 (AHSMOG men) (10) Butler, 1988 (AHSMOG women) (10) SandIer, 1989 (men) ( 11) SandIer, 1989 (women) (11) Hole, 1989 (12) Humble, 1990 (13) Steenland, 1996 (men) (3) Steenland, 1996 (women) (3) Kawachi, 1997 (4) Time I (3,4,9,12,13,18,22), four showed an increase in the RR estimate when adjusted for multiple factors besides age (9,12,13,22), whereas three showed a decrease in the RR (3,4,18).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Smokers also face a much greater risk of premature death than non-smokers [4] [5]. Unfortunately, these health implications are not the exclusive preserve of active smokers but are also shared by passive or second-hand smokers [4], [6], [7]. There are suggestions based on research that smoking tends to cause cognitive decline and results in the loss of grey matter tissue in the brain with time [8].…”
Section: Introductionmentioning
confidence: 99%